Effects of therapeutic ultrasound on pain, physical functions and safety outcomes in patients with knee osteoarthritis: a systematic review and meta-analysis. (October 2016) - Zhang, Chi; Xie, Yujie; Luo, Xiaotian; Ji, Qiaodan; Lu, Chunlan; He, Chengqi; Wang, Pu
Objective: To explore the effects of therapeutic ultrasound with sham or no intervention on pain, physical function and safety outcomes in patients with knee osteoarthritis. Data sources: This systematic review was searched on CENTRAL, EMBASE, MEDLINE, CINAHL, Physiotherapy Evidence Database, Open Gray on 4 September 2015. Trials included randomized controlled trials that compared therapeutic ultrasound with a sham or no intervention in patients with osteoarthritis of the knee. Review methods: Eligible trials and extracted data were identified by two independent investigators. Standardized mean differences (SMDs) and 95% confidence interval (CI) were calculated for pain and physical function outcomes. Heterogeneity was assessed by the I 2 test and inverse-variance random-effects analysis was applied to all trials. Results: Ten randomized controlled trials (645 patients) met the inclusion criteria. Therapeutic ultrasound showed a positive effect on pain (SMD = −0.93, 95%, CI = −1.22 to −0.64, p < 0.01, p for heterogeneity = 0.12, I 2 = 42%). For physical function, therapeutic ultrasound was advantageous for reducingWestern Ontario and McMaster Universities physical function score (SMD = −0.37, 95% CI = −0.73 to −0.01, p = 0.04, p for heterogeneity = 0.94, I 2 = 0%). In terms of safety, no occurrence of adverse events caused by therapeutic ultrasound was reported in any trial. Conclusion: The authors suggested that therapeutic ultrasound is beneficial for reducing knee pain and improving physical functions in patients with knee osteoarthritis and could be a safe treatment.